Creating an oasis: some insights into the practice and theory of a successful academic writing group. - Wardale, Dorothy; Hendrickson, T.; Klass, Des; Jefferson, Therese; Lord, Linley; Marinelli, M. (Routledge Taylor and Francis Group, 2015)
Academic writing groups are acknowledged as a successful approach to increasing research publication output and quality. However, the possible links between the formation and ongoing utilisation of writing groups and improvements in scholarly written research outputs remain relatively undertheorised. In this article, we draw on academic writing group literature, structuration theory and an analysis of the literature on characteristics of effective teams to explore the experiences of one successful academic writing group. By referring to these areas of literature and theory, we provide insights and tentative lessons that may be relevant to other academics in similar organisational contexts.